CENTRAL ASIAN UPRISING OF 1916 IN MODERN FOREIGN HISTORIOGRAPHY - Sultangalieva, G.; Koizhigitova, Zh. (Journal of history, 2018)
The article considers the uprising of 1916 in Central Asia and its study in modern foreign historiography. The aim of the article is to determine the main directions and methods used by foreign scientists in studying uprising of 1916 in Central Asia. The study is aimed identifying the approaches of foreign scientists in explaining the causes of uprising of 1916, revealing the scale of the uprising and their consequences. Authors A.Morrison, T.Kotyukova, T.Uyama, M.Olkott, X.Hallez, I.Ohayon and others have defined possibilities of further studying of an uprising of 1916 in a historical science. The results of this article can be used in the content of elective courses in the subsequent educational process and in the development of scientific articles.